Knowledge-Based Malaysian GLC: Are They More Innovative and Performing Much Better? (Malaysian Management Journal, 2009)
In the Knowledge-Age, knowledge and innovation is becoming the main driver of competitive advantage, especially for large organisations to create value and achieve prosperity. Subsequent to this, a quantitative study was conducted whereby data were collected using a mail survey sent to employees of listed Government-Linked Companies (GLCs). A total of 690 questionnaires were mailed out and 273 were returned and usable, representing a response rate of 39.5%. Using a disproportionately stratified sampling, the data collected was subject to structural equation modelling analysis. The objective was to develop and test a model of knowledge management initiatives, innovation, and performance for Malaysian GLCs. Confirmatory factor analysis was conducted to examine the validity of the measurement model and the structural model was also analysed to test the associations hypothesised in the research model. The actual findings showed that the proposed model fits the data well. Employees perceived knowledge management initiatives as important antecedents of innovation, and innovation in turn, result in better organisational performance.